Valdosta High School Scrapbook 32, August 1982 – May 1983 - Valdosta High School (My University, 1982)
This scrapbook is a collection of newspaper articles with photographs about Valdosta Highschool. The main focus of this scrapbook is the State Championship run for Valdosta High School during the season. Other sports are mentioned like cross country and basketball. Furthermore student achievements and activities.
This item contains 1 PDF file with 166 Pages and a title page in addition to 86 JPG files
Keywords: Newspapers; Photographs; Scrapbooks; Lowndes County (Ga.); Cross-country running; American Football; Basketball; Distributive Education Clubs of America